A Study of Changing Trends in Financing of Cement Industry in India - Jain, Khushpat; Shah, Kruti Aditya (SFIMAR Research Review, 2018)
Objectives: The present research attempts to study the capital structure pattern of the selected units of cement industry in India and examine the variations in the leverage ratios of these selected units for the period of 9 years from 2010 to 2018. Method: Secondary data is collected with a sample size of three Indian cement companies namely, Ultratech, Shree Cement and JK Lakshmi Cement. The data is collected from Capitaline database and the leverage ratios are calculated and then used for analysis. Result: The study points out that the debt equity ratio of JK Lakshmi Cement has showed an increasing trend over the years indicating increase in debt levels. Ultratech, Shree Cement and JK Lakshmi Cement have shown a fairly consistent debt to asset ratio. JK Lakshmi Cement has followed an increasing trend of debt to capital ratio and also of debt to EBITDA ratio. The asset to equity ratio of Ultratech has been fluctuating over the years while that of JK Lakshmi Cement has been increasing. Conclusion: It can be concluded that the all companies under study are making attempts to reduce long-term debts and maximize the wealth of the shareholders. However, JK Lakshmi Cement needs to maintain a balance of equity and debt.